Kajian Pemanfaatan dan Potensi Aplikasi Lanjut Tumbuhan Cemara Udang (Casuarina equisetifolia L.) bagi Indonesia: Studi Pustaka - Kejora Handarini; Yuyun Yuniati; Mirza Ramadhani; Achmad Kusyairi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
The abundance of flora in Indonesia is an advantage that Indonesia has, so it needs to be preserved to support the continuity of social life. Cemara udang is a conifer tree with a straight, sturdy trunk, with hanging branches and sharp green leaves which is also found in Indonesia, which borders the Indian Ocean. This species is conserved in Indonesia and is found in coastal areas, beaches and mangrove forests. Through this literature study, exploration of the empowerment of cemara udang plants is discussed. Cemara udang plants provide protection from potential adverse climates such as strong winds and soil protection. This plant also has medical benefits such as inflammation problems, digestive issues, and sore throats, and is anti-bacterial. This plant is known to have biactive compounds such as alkaloids, glycosides, saponins, flavonoids, tannins, steroids, phenolics and triterpenoids. This study also explores the potential for sustainability of cemara udang plants in Indonesia to make them more commercially efficient, as an advanced material whose potential has recently been discovered as nanoparticles for health, and as an adsorbent to overcome the problem of aquatic environments that contain a lot of residual dye.